Extensive green roofs in Colorado: plant species performance, growing media modifications, and species response to growing media dry down - Bousselot, Jennifer McGuire, author; Klett, James, advisor; Kelaidis, Panayoti, committee member; Barbarick, Kenneth, committee member; Koski, Anthony, committee member (Colorado State University. Libraries, 2010)
To view the abstract, please see the full text of the document.
Keywords: Green roofs (Gardening) -- Colorado; Plant growing media